Back Cover: Achieving Efficient Incorporation of π‐Electrons into Graphitic Carbon Nitride for Markedly Improved Hydrogen Generation (Angew. Chem. Int. Ed. 7/2019). Issue 7 (24th January 2019) - Li, Jing; Wu, Dandan; Iocozzia, James; Du, Haiwei; Liu, Xueqin; Yuan, Yupeng; Zhou, Wei; Li, Zhen; Xue, Zhaoming; Lin, Zhiqun
Abstract : Microwave‐assisted heating offers rapid heating for effective copolymerization of monomers that have a mismatch in their sublimation temperatures. In their Communication onpage 1985 ff., Y. Yuan, W. Zhou, Z. Lin, and co‐workers report a microwave‐assisted heating strategy to efficiently incorporate π‐electrons into graphitic carbon nitride for increased photocatalytic hydrogen generation.